Problems Facing Research Programme In Nigerian Tertiary Institutions - Aibe Joseph Ndayebom; B. G. Aregbesola (PT. Antis International Publisher, 2024)
This paper examined the problems facing research programme in Nigerian tertiary institutions. Secondary data were used to gather data for the paper. The data were sourced from print and online publication. The paper identified inadequate founding, infrastructure facilities, poor synergy between universities and private institutions, unattractive working conditions for research workers, insecurity, poor mentorship, corruption and mismanagement, weak research institutions, Brain-drain and poor technological advancement/ poor ICT literacy as problems militating in against reassert development in tertiary institutions in Nigeria. To solve these problems, the paper hereby recommended among others that, the government should increase the research funding in tertiary institutions in Nigeria and also create alternative sources for research funding. There is a need for multiple streams of funding, say scientists in Nigeria.